Influence of toxic leadership on knowledge hiding in Nigerian private universities: The mediating role of perceived organizational injustice - Sajuyigbe, Ademola Samuel; Inegbedion, Henry Egbezien; Tella, Rahman Adeniran; Ayeni, Adebanji William; Ojo, Olu; Morakinyo, Dauda Ayodele (Masyarakat, Kebudayaan dan Politik, 2025)
In today’s knowledge-driven economy, academic success relies on knowledge sharing, yet deliberate knowledge hiding is increasingly common in universities. This study explores the influence of perceived organizational injustice as a mediating factor in the relationship between toxic leadership and knowledge hiding among faculty members in Nigerian private universities. A purposive random sampling of 210 respondents from Nigeria’s first three private universities was conducted using a survey. Data were analyzed using Path Analysis Structural Equation Modelling (PA-SEM) in STATA version 15. The findings reveal that toxic leadership significantly promotes knowledge-hiding behaviors, evasive hiding, playing dumb, and rationalized hiding, as defensive responses. Additionally, perceived organizational injustice directly contributes to these behaviors and acts as a key mediator between toxic leadership and knowledge hiding. Faculty members who perceive unfair treatment are more likely to conceal information, feign ignorance, or justify withholding knowledge. These insights highlight the importance of fair leadership and organizational justice. For institutions to encourage open knowledge sharing, they must cultivate an environment where faculty feel psychologically safe and protected from retaliation when sharing information. Addressing leadership toxicity and organizational injustice is, therefore, critical to fostering a collaborative academic culture.